Descartes : a guide for the perplexed - Skirry, Justin (Guides for the perplexed., 2008)
Rene Descartes is arguably the most important seventeenth-century thinker and the father of modern philosophy. His seminal works are widely studied by students of philosophy. Yet his unique method and its divergence from the method of his scholastic predecessors and contemporaries raises complex and often challenging issues. Descartes: A Guide for the Perplexed is a clear and thorough account of Descartes' philosophy, his major works and ideas, providing an ideal guide to the important and complex thought of this key philosopher. The book covers the whole range of Descartes' philosophical work.